The Price of Linguistic Productivity : How Children Learn to Break the Rules of Language - Yang, Charles D. (Book collections on Project MUSE., 2016)
"All languages have exceptions alongside overarching rules and regularities. How does a young child tease them apart within just a few years of language acquisition? In this book, drawing an economic analogy, Charles Yang argues that just as the price of goods is determined by the balance between supply and demand, the price of linguistic productivity arises from the quantitative considerations of rules and exceptions. The learner postulates a productive rule only if it results in a more efficient organization of language, with the number of exceptions falling below a critical threshold. Supported by a wide range of cases with corpus evidence, Yang's Tolerance Principle gives a unified account of many long-standing puzzles in linguistics and psychology, including why children effortlessly acquire rules of language that perplex otherwise capable adults. His focus on computational efficiency provides novel insight on how language interacts with the other components of cognition and how the ability for language might have emerged during the course of human evolution"--Publisher's website.